Design of a 2-DOF delta robot for packaging and quality control of processed meat products - Balbuena, J.; Hilario, J.; Vargas, I.; Manzanares Grados, R.; Cuellar, F. (Institute of Electrical and Electronics Engineers, 2018)
The following paper describes the design, implementation and experimental results of an Automatic System for Packaging and Quality Control using machine vision in the processed meat industry. The proposed system is composed by a 2-DOF planar robot with vacuum pads to pick and place processed meat packages, a camera sensor to inspect the quality of the packages, a conveyor belt to transport the units to the robot and a linear actuator used to lift the boxes once it has full load. The proposed system picks the packages from the conveyor belt, analyzes them with a computer vision algorithm, separates the defective units and packages the products in good condition. A Graphical User Interface (GUI) is developed for controlling the system and for showing the statistics of the processed meat production, such as the percentage of defective packages, the daily quantity of production, and others. The preliminary experiments and results of the system are presented and discussed.
Keywords: Automatic packaging system; Machine vision; Quality control; https://purl.org/pe-repo/ocde/ford#2.11.03